Aplikasi Mobile Informasi Fase Bulan Dengan Perhitungan Astronomi Untuk Pengikut Kejawen - Gordon Kusuma Kahono; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2021)
The abdi (kejawen followers) still use the Javanese calendar and the moon phase for their daily needs, usually the servants use them to find a good day to perform rituals or meditation and events. The Javanese calendar is one type of lunar calendar (moon) where the calendar is based on the position of the moon. The moon is illuminated at night, and the illumination produced by the moon is different every day because the moon's illumination depends on the phase of the moon. The moon has complex parameters, namely in addition to the phase there is also the distance, and position to the Sun, and the Earth. Abdi did not understand about good ritual days, before that the servants waited for orders from the king to carry out rituals. Therefore, we need an application for moon information in the form of moon phase, moonlight, moon position along with the Javanese calendar with the Android platform. The proposed application also has features that can help abdi to perform rituals on the appropriate day. The application is also designed in a simple way so that the application is easy for abdi to understand. To obtain lunar information, an astronomical calculation system is used, where for the initial data obtained from astronomical calculations in 1990 for moon and sun data. The results of the application have been tested with moon information with test data, with the result that the difference from moonlight is 0.2%. The results of the application have been surveyed to determine the level of user satisfaction. Abdi will be helped by the application features provided.